Should we be concerned with spam emails? A look at its impacts and implications - Bujang, Yanti Rosmunie; Hussin, Husnayati (2013)
As the most popular communication technology, email has been widely used by the Internet users. Most past researches on email has focused on major problems of email misuse such as spam emails and email overload. Technology-based papers focused on how to filter emails so that spam is minimized. In reality, however, most email users are not aware of the implications of spam problem because the impacts are not clearly visible to an individual. At the organizational level or higher, the impacts of spam emails are even more serious as it has financial implications. This paper aims to discuss the spam email problems from the social and behavioral perspective and highlight the impacts of the spam email on individuals, organization and the society in general. The understanding on how the email users’ deal with the spam email currently has revealed their weaknesses when dealing with spam. Some recommendations are also proposed to encourage the good ethics in dealing with emails. It aims to instill the awareness and hope that email users can take proactive steps to protect their inbox.